2001
DOI: 10.1002/cjg2.185
|View full text |Cite
|
Sign up to set email alerts
|

Current Horizontal Deformation And Motion Mechanism Of Major Tectonic Units And Boundary Zones in North China

Abstract: Based on the data obtained from the high‐precision GPS measurements carried out in 1992,1995,1996 and 1999 in North China, the relative horizontal motion occurred in two periods (1992–1996 and 1996–1999) botteen the major tectonic units in North China is given in the paper. The results are as follow: (1) Relative to the Ordos unit, the movement of Yinshan unit is of relatively weak left‐lateral strike slip with the amplitude of (0–2.3) ±1.6mm/a and the orientation of about 0°–W13 °N; (2) Relative to Ordos unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…4-6, we can see that the significant maximum strain rate distributions are located mainly in three places, to the north of Tangshan, between Tianjing and Shijiazhuang, and to the north of Datong. This agrees with geological investigation results, showing that these three places are located in the Holocene active crustal movement area (Yang et al, 2001). Significant dilation and compression centres are also located in these three areas (Fig.…”
Section: Strain Distribution and Analysissupporting
confidence: 89%
“…4-6, we can see that the significant maximum strain rate distributions are located mainly in three places, to the north of Tangshan, between Tianjing and Shijiazhuang, and to the north of Datong. This agrees with geological investigation results, showing that these three places are located in the Holocene active crustal movement area (Yang et al, 2001). Significant dilation and compression centres are also located in these three areas (Fig.…”
Section: Strain Distribution and Analysissupporting
confidence: 89%
“…1). From Yang et al [37] , Ordos block is in the west of Taihang uplift, Jiaoliaolu block is in the east of Taihang uplift, and North China basin is part of Shanxi-Hebei-Shandong block. Wang et al [35] made a comprehensive study of the stress field of Chinese mainland in the 20th century and then indicated that the principal compressional stress is nearly E-W in North China.…”
Section: Shear-wave Splitting In Northwest Capital Areamentioning
confidence: 98%
“…Apparently, its special tectonic setting and intricate crustal structure are the consequence of tectonic changes and lithospheric thinning in the Mesozoic. At present this region is still very active in tectonic movement as well as seismicity [17,18] . Since the historical records, it has been attacked by more than 100 M ≥ 5.0 earthquakes, including 35 M ≥6.0 and 7 M ≥7.0.…”
Section: Introductionmentioning
confidence: 96%